Effect of full-fat corn germ and Vitamin E on finishing performance and carcass characteristics of beef heifers - Sean P. Montgomery; J.J. Sindt; M.A. Greenquist; E.J. Good; E.R. Loe; M.J. Sulpizio; T.J. Kessen; James S. Drouillard; Brandon E. Depenbusch (Kansas Agricultural Experiment Station Research Reports, 2003)
Eight hundred eighty-eight crossbred beef heifers weighing 837 lb were used in a 105- day finishing study to evaluate full-fat corn germ as a lipid source and added vitamin E in finishing diets containing steam-flaked corn. Treatments were arranged in a 2 x 4 factorial and consisted of finishing diets formulated to provide no added fat (Control), 4% tallow (Tallow), or 10% or 15% full fat corn germ on a dry matter basis (10%FFG and 15%FFG, respectively) with or without 2000 IU of additional vitamin E per heifer daily. No fat x vitamin E interaction was detected. Fat addition decreased (P0.12). This study suggests that full fat corn germ can serve as a supplemental lipid source for finishing cattle. Responses to 10% full fat corn germ were similar to those obtained when an equal amount of fat from tallow was incorporated into the diet.
Keywords: Cattlemen' s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Vitamin E; Full-fat corn germ; Finishing performance; Carcass characteristics; Heifers